’Adaptive Authoritarianism’ in Contemporary China: Identifying Zones of Legitimacy Building - Ahlers, Anna Lisa; Schubert, Gunter (Reviving Legitimacy: Lessons for and from China, 2011)
Anna L. Ahlers and Gunter Schubert, ’Adaptive Authoritarianism’ in Contemporary China: Identifying Zones of Legitimacy Building, in: Deng Zhenglai and Guo Sujian (eds), Reviving Legitimacy: Lessons for and from China, Lanham: Lexington Books (2011),

How China Escaped the Poverty Trap - Ang, Yuen Yuen (Cornell University Press, 2016)
Before markets opened in 1978, China was an impoverished planned economy governed by a Maoist bureaucracy. In just three decades it evolved into the world's second-largest economy and is today guided by highly entrepreneurial bureaucrats. In How China Escaped the Poverty Trap, Yuen Yuen Ang explains this astonishing metamorphosis. Rather than insist that either strong institutions of good governance foster markets or that growth enables good governance, Ang lays out a new, dynamic framework for understanding development broadly. Successful development, she contends, is a coevolutionary process in which markets and governments mutually adapt.By mapping this coevolution, Ang reveals a startling conclusion: poor and weak countries can escape the poverty trap by first harnessing weak institutions―features that defy norms of good governance―to build markets. Further, she stresses that adaptive processes, though essential for development, do not automatically occur. Highlighting three universal roadblocks to adaptation, Ang identifies how Chinese reformers crafted enabling conditions for effective improvisation.How China Escaped the Poverty Trap offers the most complete synthesis to date of the numerous interacting forces that have shaped China’s dramatic makeover and the problems it faces today. Looking beyond China, Ang also traces the coevolutionary sequence of development in late medieval Europe, antebellum United States, and contemporary Nigeria, and finds surprising parallels among these otherwise disparate cases. Indispensable to all who care about development, this groundbreaking book challenges the convention of linear thinking and points to an alternative path out of poverty traps.
Keywords: IMPORTANT

Signal Left, Turn Right: Central Rhetoric and Local Reform in China - Huang, Haifeng (Political Research Quarterly, 2013)
How have local governments in China been able to break through central policy restrictions in a unitary and authoritarian political system? Why is China's official discourse in the reform era often so conservative and unfavorable to reform? The author argues the two issues are components of a signaling game between China's central government and local officials, in which local officials know that the center may be reformist, but the reformist center imitates the rhetoric of a conservative center to control the pace of local liberalization. The result is a gradualist reform of "signaling left, turning right," with glaring incongruity of speech and actions in the process.

Policy experimentation and innovation as a response to complexity in China’s management of health reforms - Husain, Lewis (Globalization and Health, 2017)
There are increasing criticisms of dominant models for scaling up health systems in developing countries and a recognition that approaches are needed that better take into account the complexity of health interventions. Since Reform and Opening in the late 1970s, Chinese government has managed complex, rapid and intersecting reforms across many policy areas. As with reforms in other policy areas, reform of the health system has been through a process of trial and error. There is increasing understanding of the importance of policy experimentation and innovation in many of China’s reforms; this article argues that these processes have been important in rebuilding China’s health system. While China’s current system still has many problems, progress is being made in developing a functioning system able to ensure broad population access. The article analyses Chinese thinking on policy experimentation and innovation and their use in management of complex reforms. It argues that China’s management of reform allows space for policy tailoring and innovation by sub-national governments under a broad agreement over the ends of reform, and that shared understandings of policy innovation, alongside informational infrastructures for the systemic propagation and codification of useful practices, provide a framework for managing change in complex environments and under conditions of uncertainty in which ‘what works’ is not knowable in advance. The article situates China’s use of experimentation and innovation in management of health system reform in relation to recent literature which applies complex systems thinking to global health, and concludes that there are lessons to be learnt from China’s approaches to managing complexity in development of health systems for the benefit of the poor.

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.